Immobilisation of Acetylcholinesterase onto Electrospun Nanofibres for Carbofuran and Demeton-S-Methyl Sulfone Detection - Mafuma, Tendai; Susan van Dyk, J.; Chigome, Samuel; Torto, Nelson; I. Pletschke, Brett (Current Biotechnology, 2015)
Electric eel acetylcholinesterase (AChE) was immobilised on electrospun nylon 6: chitosan nanofibres using glutaraldehyde (GA) cross-linking. The immobilisation protocol was optimised and a GA solution of 5% (v/v) resulted in the immobilisation of 0.334 mg/cm2 of AChE onto the nanofibres. The immobilised enzyme was characterised with respect to pH and temperature and results compared to the free enzyme. The Vmax values obtained for the free and immobilised AChE enzymes were 0.345 and 0.287 µmol/min/mL, respectively, and the Km values for the free and immobilised AChE enzymes were 0.482 and 0.812 mM, respectively. Relative to free AChE, the immobilised enzyme showed considerable storage stability retaining 50% of its activity when stored for 49 days at 4°C. Immobilised AChE also retained > 20% of its initial activity after 9 consecutive reuse cycles. When exposed to fixed concentrations of pesticides (carbofuran and demeton-S-methyl sulfone), immobilised AChE showed almost identical inhibition characteristics compared to the free enzyme. In conclusion, nylon-6:chitosan electrospun nanofibres were shown to be suitable supports for facile AChE immobilisation and the immobilised enzyme has potential for use in pesticide detection.
Keywords: nylon